Revisiting Sustainability of Fungicide Seed Treatments for Field Crops - Lamichhane, Jay Ram (Plant disease, 2020)
The use of fungicide seed treatment (FST) is a very common practice worldwide. The purported effectiveness of many fungicides in providing broad-spectrum and systemic control of important diseases and the perception that FST reduces overall pesticide use, hence lowering environmental impacts, have greatly promoted the use of FST in the last five decades. Since there have been rapid advancements in the types, formulations, and application methods for seed treatments, there is a need to re-evaluate the benefits versus the risks of FST as a practice. While the use of seeds treated with neonicotinoid insecticides has come under scrutiny due to concern over potential nontarget effects, there are knowledge gaps on potential negative impacts of FST on operators' (those who apply, handle, and use treated seeds) health and nontarget soil organisms (both macro- and microorganisms). Here we review existing knowledge on key fungicides used for seed treatments, benefits and risks related to FST, and propose recommendations to increase benefits and limit risks related to the use of FST. We found FST is applied to almost 100% of sown seeds for the most important arable crops worldwide. Fungicides belonging to 10 chemical families and with one or several types of mobility (contact, locally systemic, and xylem mobile) are used for seed treatment, although the majority are xylem mobile. Seed treatments are applied by the seed distributor, the seed company, and the farmer, although the proportion of seed lots treated by these three groups vary from one crop to another. The average quantity of fungicide active ingredient (a.i.) applied via seed treatment depends on the crop species, environment(s) into which seed is planted, and regional or local regulations. Cost-effectiveness, protection of the seed and seedlings from pathogens up to 4-5 weeks from sowing, user friendliness, and lower impact on human health and nontarget soil organisms compared with foliar spray and broadcast application techniques, are among the most claimed benefits attributed to FST. In contrast, inconsistent economic benefits, development of resistance by soilborne pathogens to many fungicides, exposure risks to operators, and negative impacts on nontarget soil organisms are the key identified risks related to FST. We propose eight recommendations to reduce risks related to FST and to increase their benefits